Projeto - Geraldo Augusto Fernandes (Medievalista)
The purpose of this informative article is to present the REPERTÓRIO MÉTRICO of Garcia de Resende’s Cancioneiro Geral. Resende’s compendium is made up of 880 poems, and their forms can be defined by ‘cantigas’ (songs), ‘baladas’ (ballads), ‘trovas’, ‘vilancetes’ and ‘poemas de formas mistas’ (poems of mixed forms). The project includes the presentation of the origins and evolution of each of these forms, followed by the presentation of all poems of the same formal classification. For each poem, the data of the poem and volume number and its authorship. Next, the elements of versification: stanzas, verses, complete composition of the stanza/verses, meter, genre (when possible), language, ‘pés quebrados’ (broken feet) (when available). To close the repertoire, the rhymes and the rhyme scheme. This project is inspired in Giuseppe Tavani’s Repertorio Metrico, in which the author presents the rhymes and rhyme schemes of Galician-Portuguese troubadour ‘cantigas’. This project, however, will take into account more aspects that were not contemplated by the Italian scholar. For this article, I will use the POEMAS DE FORMAS MISTAS as an example, demonstrating their origins, evolution and persistence in the 15th/16th centuries.